Synthesis of Amphiphilic Triblock Copolymers by ATRP and Coalescence Suppression Effect in Suspension Polymerization - Eri Fujita; Kosuke Kaneko; Tsubasa Oshima; Daiki Fujioka; Kimiyoshi Kaneko; Kiyomi Fuchigami; Tomonori Hanasaki (Journal of Chemical Engineering of Japan, 2023)
In this study, the role of amphiphilic triblock copolymers in suppressing the coalescence of the polymers obtained by suspension polymerization was systematically investigated through the preparation of polymer beads using a common monomer (methyl methacrylate). First, a series of amphiphilic triblock copolymers (PAA-b-PS-b-PAA) were synthesized by atom transfer radical polymerization (ATRP). After synthesizing macroinitiators (PS), the corresponding amphiphilic triblock copolymers were prepared with varied numbers of hydrophobic and hydrophilic units. Subsequently, suspension polymerization was conducted to synthesize polymer beads using the obtained amphiphilic triblock copolymers as polymeric surfactants. We clarified the role of the amphiphilic triblock copolymers in suppressing coalescence of each bead, by observing the size of the monomer droplets prior to suspension polymerization and that of the resulting polymer beads with a microscope.